Dinamika Penjatuhan Talak Melalui Whatsapp dalam Paradigma Pembaharuan Hukum Keluarga Islam - Ahmad Ropei; Ramdani Wahyu Sururie (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2021)
This article aims to describe the paradigm of Islamic family law reform against the dynamics of the imposition of divorce through WhatsApp  media, one of the problems often faced in various divorce cases. This paper is classified as a qualitative type, with the approach used being library research. Data analysis was carried out using descriptive-analytical techniques. The results of this article indicate that the adoption of divorce via WhatsApp according to most legal scholars is valid with the qiyas approach as the delivery of divorce through writing in the form of a letter. Meanwhile, in the paradigm of reforming Islamic family law in Indonesia, the imposition of divorce via WhatsApp  is considered invalid, considering that the validity of the divorce is only recognized when it is sworn in before the court. This paradigm is based on various efforts to achieve the benefit, especially to avoid arbitrary actions by the husband against his wife unilaterally in terms of imposing divorce and obtaining legal legality.